Trans Driver Stress scale (TDS-15): Short scale for stress detection in professional drivers. (October 2018) - Serrano-Fernández, María-José; Boada-Grau, Joan; Robert-Sentís, Lluís; Boada-Cuerva, Maria; Assens-Serra, Jordi; Vigil-Colet, Andreu
Highlights: The TDS-15 assesses stress in professional drivers. The TDS-15 can be applied and interpreted quickly and easily. It must be taken into account by HR in passenger transport companies. The scale has good psychometric properties, The result allows to obtain reliable data for assessments based on scientific evidence. Abstract: Background: Professional drivers are susceptible to stress, which places both their own health and road safety at risk. For this reason the present study aims to create a short Spanish scale from the 59 items on the Bus Driver Risk Index (BDRI; Dorn, Stephen, af Wåhlberg, & Gandolfi, 2010), and to analyse its internal structure, reliability and evidence of validity. Method: The participants were 372 Spanish drivers (93.4% male, 6.6% female), obtained by non-probabilistic sampling. The programs SPSS 20.0 and AMOS (5.0) were used. Results: The Trans Driver Stress scale (TDS-15) provides a five-factor solution with 15 items, adequate reliability and appropriate evidence of validity. Through a confirmatory factor analysis, the following indicators (NFI = 90, TLI = .92; CFI = .91; RMSEA = .06) were obtained from the AMOS program (5.0) indicating that the five factor model has an acceptable fit. Evidences of validity are also proved with: SSQ-15, MBI-GS, Irritation, MP-9, DII and Trans-18. Conclusions: The Trans Driver Stress scale (TDS-15) is a reliable and valid instrument, suitable for use in Spanish to evaluate the stress experienced by professional drivers in the transport industry.